Analisis Mutu Pelayanan Keseshatan Rawat Inap Di Rumah Sakit Muhammadiyah Bandung - Fatimah Khodimatudinni Haqiqi; Eka Purwanda (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2023)
A hospital is a place to provide short-term and long-term medical services which include diagnostic, therapeutic, observation and rehabilitation activities for all people who are sick or injured and for those who give birth and outpatient services for those who need them according to their illness. The purpose of this study was to determine and analyze the quality of inpatient health services at Muhammadiyah Bandung Hospital. According to Parasuraman, Zeithaml, and Berry through their research identified 5 main dimensions, namely reliability, responsiveness, guarantee, empathy, and tangible. This study uses a type of qualitative research with case studies. Service reliability at the hospital is that there are still doctors who are not on time because there are doctors' practice schedules at other hospitals, responsiveness at the hospital is that there is still a lack of 5S implementation, especially for greetings, assurance (Assurance) at the hospital that is, officers still do not fully comply with applicable regulations, empathy (empathy) in the hospital is treating patients according to their needs and responding to complaints openly, namely accepting criticism and suggestions, physical evidence (tangibles) is the existing infrastructure in the hospital, the completeness is still around 70% in terms of hospital type.